Photocatalytic removal of phenol over porous Zno/Tio2 composites - Klinsmann, Cheong Lee Khang, 1993- , author (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2017)
Project Paper (Sarjana Muda Sains (Kimia Industri)) - Universiti Teknologi Malaysia, 2017